Conditional constructions in Buwal - Melanie Viljoen (LibraryPress@UF, 2017)
This study examines the structure of conditional constructions in Buwal and their functions. Conditionals in Buwal can be divided into four major categories according to how they are marked: possible, counterfactual, necessary and concessive. Possible conditionals include both reality and unreality conditionals. The usual order is for the protasis to precede the apodosis, but the reverse order is also possible. All types of tense/aspect marking are possible in both the protasis and the apodosis with variations arising from semantic rather than grammatical restrictions. The possible conditional marker can also function as a temporal marker in certain contexts. In a conditional construction, the protasis provides a framework or background for the apodosis.